Kaitan Kebiasaan Makan dan Aktivitas Fisik pada Remaja dengan Kejadian Gizi Lebih di Smpn 1 Kota Bengkulu - Dinda Martiana Salsabiila; Tetes Wahyu Witradharma; Emy Yuliantini (JGK:Jurnal Gizi dan Kesehatan, 2023)
Background: Nutrition is more commonly known as obesity is a condition where the calories consumed are more than the calories used causing excessive accumulation of fat in the body which can result in health problems. Objective: This study plans to find out information about excess nutrition in adolescents, especially junior high school students, regarding the relationship between eating habits and physical activity with the incidence of overweight Methods: The population in this study were class 7 and 8 with a total sample of 62 people with a cross sectional study design. Data analysis used bivariate analysis using the Chi Square tes.t. Results: there are more unhealthy eating habits than good habits, while for very light physical activity there are more than light activities. Conclusion: There is a relationship between eating habits and physical activity with the incidence of overweight in junior high school adolescents. Poor eating habits and very little physical activity can potentially lead to over nutrition.